2D:4D digit ratio and its relations to cross-sex and same-sex friendship choices. (1st November 2018) - Altmann, Tobias; Roth, Marcus
Abstract: The 2D:4D digit ratio is a sexually differentiating biomarker for prenatal testosterone, which affects structural and functional aspects of individual brain development. Previous studies have shown that 2D:4D is associated with personality traits and aspects of social behavior (e.g., mating). The present study extends this approach to friendship ties as an example of social relationship outcomes. On the basis of the previous finding that 2D:4D is associated with sex drive, we expected men and women to show differential relations between 2D:4D and numbers of cross-sex and same-sex friends. 265 heterosexual adults took part in the study. 2D:4D was differentially related to friendship types for men and women. The hypotheses were partly supported such that male-typed (i.e., low 2D:4D) men had fewer close same-sex friends and larger numbers of general cross-sex friends than female-typed men did. Similarly, female-typed (i.e., high 2D:4D) women showed larger numbers of close same-sex friends than male-typed women did. In summary, the relations between 2D:4D and friendship ties provide further support for the claim that social behavior is affected by prenatal hormone stimulation at least to some extent.